Transcripts of the Sacred in Nigeria: Beautiful, Monstrous, Ridiculous. - HACKETT, ROSALIND I. J. (International Journal of African Historical Studies, 2024)
The article reviews two books, "Transcripts of the Sacred in Nigeria: Beautiful, Monstrous, Ridiculous" by Nimi Wariboko and "Creole Language, Democracy, and the Illegible State in Cabo Verde" by Abel Djassi Amado. Wariboko's book explores the concept of the sacred in Nigeria, challenging conventional narratives and focusing on human flourishing in the postcolonial context. Amado's work delves into the relationship between language, state-making, and democracy in Cabo Verde, highlighting the impact of language policy on governance and inequality. Both books offer unique perspectives on African studies and language politics, providing valuable insights for researchers in these fields.